Tools of the Trade: Intellectual Property Issues in Electronic Commerce Tools - Harrison Dinniss, Heather A (Victoria University of Wellington Law Review, 2001)
This article explores some of intellectual property issues that arise out of the use of electronic commerce technology and tools. Part II of the article looks at the issues of ownership in the electronic commerce structure. The author examines the grant of patents for technology underlying the Internet and the emerging practice of granting patents for Internet business methods. Part III of the article explores the intellectual property issues which arise out of the use of associational tools such as hyperlinking, meta tags, framing and inline linking. These techniques are the tools of the trade for web site developers and lawyers seeking advise clients in relation to electronic commerce should be aware of the issues.